2016
DOI: 10.1159/000449239
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss after Round Window Surgery in Mice Is due to Middle Ear Effusion

Abstract: Background: Delivery of therapeutic agents directly through the round window (RW) offers promise for treating sensorineural hearing loss. However, hearing loss can result from the surgical approach itself, and the reasons for this are poorly understood. We examined the hearing loss following the 3 major steps involved with the RW approach to access the mouse cochlea: bullostomy, RW puncture, and RW injection. Methods: Twenty-one adult CBA/J mice underwent bullostomy alone, 10 underwent RW puncture, and 8 under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The adult mouse otic capsule was completely ossified (in contrast to the neonatal mouse otic capsule, which is cartilaginous). Therefore, the adult mouse inner ear gene delivery was done using the round window approach 13,27,28 . A post-auricular incision was made using small scissors.…”
Section: Methodsmentioning
confidence: 99%
“…The adult mouse otic capsule was completely ossified (in contrast to the neonatal mouse otic capsule, which is cartilaginous). Therefore, the adult mouse inner ear gene delivery was done using the round window approach 13,27,28 . A post-auricular incision was made using small scissors.…”
Section: Methodsmentioning
confidence: 99%
“…The latter 2 methods have an advantage in that they deliver directly to the perilymphatic system, bypassing adsorption barriers, though, at the same time, these may be considered more invasive and with more potential risks than systemic or intratympanic delivery approaches. Indeed, round window injection has variable efficacy, possibly due to the increased risk of middle ear effusion [31]. Canalostomy may have some advantages for drug delivery directly to the inner ear without the risk for hearing loss [22,32].…”
Section: Treatment Of Inner Ear Dysfunctionmentioning
confidence: 99%
“…The viral vectors are, thus, in contact with the basilar membrane, from where they can pass to the endolymphatic space and reach the targeted cells. However, a transient elevation of hearing thresholds is often observed after opening the RWM and injecting viral vectors in adult mice [65,66]. Xia et al [67] showed that opening the RWM followed by injection of viral vectors did not induce cochlear damage in neonatal mice.…”
Section: Round Window Injectionmentioning
confidence: 99%
“…For the successful clinical translation of gene therapy for treating or preventing inner ear genetic diseases, important questions such as off-target side effects, biodistribution of vector components, and the risk of carcinogenesis remain to be addressed through preclinical trials used in non-human primates or humanized models such as: (i) explants of human adult cochlear epithelium from surgical resection of the cochlea or from donors in the state of brain death, and (ii) inner-ear organoids generated from human-derived iPSCs [65,66] or from deaf patients. The generation of in vitro pathological models for each genetically deaf patient would allow transitions into personalized and precise medicine.…”
Section: Future Directionsmentioning
confidence: 99%